Association of Metabolic Syndrome with Increased Cardiovascular Risk in Hypothyroidism Patients: Evidence from a Nepalese Population - Jha, Bipin Kumar; Lamichhane, Anit; Shrestha, Saguna Laxmi Tandukar; Maharjan, Sabindra; Joshi, Govardhan; Adhikari, Nitesh; Khadka, Anil; Bista, Pabitra; Thakur, Rajesh Kumar; Khanal, Sudip; Gautam, Sujan; Acharya, Aashish; et al. (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Hypothyroidism is associated with metabolic syndrome and increased cardiovascular disease (CVD) risk worldwide. This study is conducted to assess hs-CRP as a CVD risk marker in hypothyroidism patients with and without metabolic syndrome.Method: A cross-sectional study was conducted at Manmohan Memorial Teaching Hospital, Kathmandu, Nepal involving 244 participants where 122 euthyroid controls and 122 with hypothyroidism cases. Anthropometric data, blood pressure, fasting glucose, lipid profile, thyroid hormones, and hs-CRP were analyzed.Results: Individual with hypothyroidism showed significantly increased level of DBP, WC, FBS, TC, TG, LDL, and hs-CRP, and lower HDL levels (p